EFFECT OF POTASH FERTILIZATION AND FOLIAR APPLICATION OF IRON AND ZINC ON YIELD AND QUALITY OF TWO GENOTYPES OF MUNG BEAN - & Al-Jumaily, Abdalgafor (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A filed experiment was conducted at Ehssay village-Amria-Fallujah district in Al-Anbar governorate during the spring season of 2012 and 2013 in order to study the effect of potassium fertilizer and foliar nutrition of iron and zinc on yield and its quality of two mung bean (Vigna radiata L.) genotypes. Factorial arrangement was used in RCBD with three replicates. The experiment included three levels of potassium (0, 60 and 120) kg K.ha-1, four treatments of foliar application of zinc and iron (0, Fe 150, Zn 100 and Fe 150 + Zn 100) mg.L-1 and two mung bean genotype (Local and Indian VC6089A10). The local genotype gave the highest rate of the number of pods (32.13 and 36.28) pod.plant -1and seed yield (573.0 and 601.8) kg.ha-1, while the indian genotype was superior in weight of 100 seed (6.66 and 7.29) gm for both seasons respectively. The level 60 kg K.ha-1 of potassium gave the highest average of seed yield (635.4  and 663.6) kg.ha-1, while the level 120 kg.ha-1 gave heighest average of number of seeds per pod (7.6 and 7.5 seed.pod-1) and protein percentage (26.18 and 25.82)% for the two seasons respectively. The concentration of Fe 150 mg Fe.L-1 and Fe + Zn (Fe 150 + Zn100 mg.L-1) recorded highest values for most of yield traits for both seasons. The foliar application of Fe gave seed yield (583.0 and 576.8) kg.ha-1, while foliar application of Fe+Ze gave highest average of seed per pod (7.6 and 7.2) seed.pod-1 and percentage of protein (27.17 and 27.11)% for both seasons respectively. A significant interaction between genotypes and potassium levels, the local genotype with 60 kg K.ha-1gave the heighest average of the number of pods (39.22 and 41.61) pod.plant-1 and seeds yield (703.6 and 756.9) kg.ha-1 for both seasons respectively, so the interaction between local genotype and concentration (Fe150 + Zn100) mg.L-1 gave the highest average of number of pods, number of seeds per pod and protein percentage for the first seasons only. The interaction between the level 60 kg K.ha-1 of potassium and the concentration Fe150 mg.L-1 from the foliar nutrition of iron showed significant superiority in seed yield (754.9 and 759.5) kg.ha-1 for both seasons respectively. The triple interaction was significant in most of traits under study, the local genotype that fertilized with 60 kg K.ha-1 and sprayed with Fe 150 + Zn 100 mg.L-1 gave highest average of seed yield (886.7 kg.ha-1) in the second season only.